(3GdYQa aj SQ GdMQas - (3eLghds ((3GdedG Ydj GdedG OQhjTs)
(3ChdgG (B:s
(3ChdgG(B: (3GdMeO ddg ehOY GdCSQGQ dChdjGFg GdCNjGQ djJUQahG HZPfg aj Ndbg HeG jMH hjNJGQ (B... (3hQJHJgG Ydi ebOeI heWdHjf hNGJeI, CeG GdebOeI aaj Yde GdCYeGds
(3BNQgG (B:s
(3BNQgG(B: (3hcPG fGQG CMGW Hge SQGObgG hEf jSJZjKhG jZGKhG HeGA cGdegd jThj GdhLhg hSGAGJ eQJabGs
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
(3ehGUaGJ GdfSNI (B: s
(3ceGd GdfSNI (B:s
Keywords: (3GdMQha hGdChaGbs